Kepuasan Siswa Sma (Peserta Program Kunjungan) Terhadap Kinerja Media Promosi Institut Pertanian Bogor - Rio Fatahillah Chita Putra; Pudji Muljono; Anna Fatchiya (Institut Pertanian Bogor, 2015)
Information has become one of the main needs of the community. Now, the trend of high school students in selecting agricultural major, has decreased. Promotion media of university is very important to improve the information, knowledge, and interests of students in selecting agricultural major in university. This study was conducted to know about the performance of promotion media of IPB. This study used a quantitative approach with survey research method. Data analysis methods used correlational descriptive and gratification discrepancy analysis (T-Test). Data collecting used questionnaire to 112 high school student who participants of “visit program”to IPB. The result shows there any differences of student gratification level toward presentation media, Facebook, and Twitter. Presentation media can use as main media in IPB promotion activity, because based on result of gratification discrepancy, the performances was good and significant. Presentation media can use as mainstream media promotion of IPB.Keyword: gratification, high school students, performance, promotion media, university